Analysis of adverse events with ruxolitinib using real-world datasets and drug-interaction networks - Hideyuki Tanaka; Mika Maezawa; Mizuki Tanaka; Ryogo Umetsu; Sakiko Hirofuji; Koumi Miyasaka; Satoshi Nakao; Yuka Nokura; Moe Yamashita; Nanaka Ichihara; Kana Sugishita; Tomofumi Yamazaki; et al. (SAGE Open Medicine)
Objectives: Ruxolitinib is used to treat myelofibrosis, polycythemia vera, and steroid-refractory graft-versus-host disease following allogeneic stem cell transplantation. This study aimed to determine the association between ruxolitinib and adverse events by evaluating case reports published between January 2014 and March 2024 in the Japanese Adverse Drug Event Report database. Methods: The signals for the ruxolitinib–adverse event association were identified using propensity score-adjusted reporting odds ratio analysis. Data obtained from the drug–gene interaction, drug signature, search tool for chemical interactions, and interaction reference index databases were used to construct a drug–gene interaction network. Functional and pathway enrichment analyses were performed using the Disease Ontology Semantic and Enrichment and ReactomePA R packages. Results: The propensity score-adjusted reporting odds ratio for ruxolitinib-associated adverse events was as follows: anemia, 18.49 (95% confidence interval (CI): 16.15–21.16); myelosuppression, 4.70 (95% CI: 3.54–6.24); pancytopenia, 1.97 (95% CI: 1.23–3.16); cardiac failure, 2.29 (95% CI: 1.60–3.28); hepatic function abnormal, 1.60 (95% CI: 1.15–2.23); herpes zoster, 6.40 (95% CI: 4.35–9.41); pneumonia, 2.96 (95% CI: 2.35–3.73); renal impairment, 1.34 (95% CI: 0.94–1.90); sepsis, 5.14 (95% CI: 3.75–7.05); interstitial lung disease, 0.33 (95% CI: 0.21–0.52); deep vein thrombosis, 0.32 (95% CI: 0.07–1.44); hemorrhage, 1.99 (95% CI: 1.05–3.75). We also assessed 3015 human genes that directly or indirectly interact with ruxolitinib. The molecular complex detection plug-in of Cytoscape was used to detect 24 clusters. Several genes were enriched in the biological processes of “anemia” and “bacterial infections,” identified as significant ruxolitinib-related disease terms. Conclusions: This retrospective analysis using the Japanese Adverse Drug Event Report database indicated potential associations between ruxolitinib and adverse events, including anemia and bacterial infections. Future research should explore the underlying pharmacological mechanisms using functional enrichment analysis of ruxolitinib-associated genes related to blood toxicity and bacterial infections.